Flow Pattern Classification in Lymphatic Malformations by Indocyanine Green Lymphography. Issue 3 (March 2019) - Kato, Motoi; Watanabe, Shoji; Iida, Takuya; Watanabe, Azusa
Abstract : Background: Lymphatic malformation is a congenital lymphatic disorder. Although a few lymphangiographic and lymphoscintigraphic studies of lymphatic malformation exist, its lymphatic flow has not been fully assessed, and a classification system has not yet been established. However, indocyanine green lymphography has been developed to safely provide a fine assessment of lymph flow in the treatment of lymphedema. In addition, indocyanine green lymphography has been shown to be helpful in detecting the lymphatic malformation inflow for the treatment of refractory microcystic type lymphatic malformation using the venous anastomosis technique. Therefore, the authors aimed to reveal the in vivo lymph flow around the lymphatic malformation using indocyanine green lymphography, and to design a classification system according to the observed patterns. Methods: Indocyanine green lymphography was performed in 20 sequential pediatric patients with lymphatic malformation (aged 11 months to 10 years). Most of the cases were intractable, with microcystic or mixed-type lymphatic malformation. Results: All patients successfully completed lymphography with clear observations. The flow patterns were classified into four types: type 1 had a strong detectable inflow; type 2 had multiple small observable inflows; type 3 had a superficial lymph flow over the lesion; and type 4 had a flow around the lymphatic malformation, without any connections to the lesion. Conclusion: The proposed classification system may aid in the further development of surgical treatments for lymphatic malformation.